Establishing Educational Robotics Labs in Iraqi Universities - Ghada Saleem (QALAAI ZANIST JOURNAL, 2021)
The Iraqi universities are seeking to develop the education and catching up with the scientific progress and technological advances in the industrialized countries. One of the most important goals of education development is to graduate students capable of competition in the labour market, and participate in the society development. The Iraqi universities aimed to give the students level of experience depending on the basis of scientific knowledge to help students solve the real world problems. The universities also seek to provide education linking the individual with the environment and economic requirement. The mission of the Educational Robotics Lab. at the University of Baghdad is to provide students a rigorous, interdisciplinary learning environment focused on Science, Technology, Engineering, Mathematics (STEM), to foster the joy of discovery, and to promote a collaborative culture of innovative problem solving. STEM education plays a big role as the catalyst to meet the challenges and demands of our present and future economy.